Effect of Different Packaging Films on Storability of Mushroom (Agaricus bisporus) - R. Aminzadeh (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2014)
The button mushroom is rich food full of nutrient but compared with other fruits and vegetables, mushroom has a higher respiration rate and due to the lack of protective layer to prevent water loss, decay occurs quickly. It seems that suitable coating film is the one way for increase the storage life of mushroom. Therefore present research was carried out as split plot design in farme of CRD to find the best coating film in order to increase the storage life. In this research, the treatments were: control (package with Selefon), Poly Ethylene (PE) with 40 and 65 micron thickness, Biaxially Oriented Polypropylene (BOPP) with 25, 35 and 40 micron thickness, Cast PolyPropylen (CPP) with 25 and 40 micron thickness, Poly Ester (PET) with 12 and 24 micron thickness and Poly Vinyl Chloride (PVC) with 30 micron thickness. The samples were estimated after 0, 10, 15, 20 and 25 days storage at 1°C and 90 % RH in 3 replications. The results showed that the types of plastic coating had significant effects on all measured characteristics as campared to that of control. Highest firmness value, Soluble Solid Content (SSC), titratable acidity, acidity (pH), and lowest weight less and decay were observed in packet mushroom with the coating film: BOPP and CPP and the lowest amounts were observed in the mushroom packed with control, PVC, PET and PE films. The effects of time on all of the measured during the storage period, were significant too.